2014
DOI: 10.5861/ijrse.2014.838
|View full text |Cite
|
Sign up to set email alerts
|

Attitude influence on performance in technical skill acquisition among formal technical trainees

Abstract: This cross-sectional study analyzed attitude influence on performance in technical skill involved in a specific trade chosen among all the formal technical trainees of Don Bosco Technical Institute (DBTI), Onitsha, Nigeria. This study was carried out between May and July, 2013. The 24-item questionnaire, designed after critical examination and revision of some related studies and a combination of individual technical projects, sequence of job operation prepared by the students and written tests which cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Major factors which affect the attitude of students toward technical subjects were interest, gender, socio-economic status among others. 127 Aysem and Fatma 115 reported that a significant relationship can be found between students’ attitude toward their study and many demographical variables. Micheal 128 reported that there is no evidence that there is a difference in the perception of male and female students on the four dimensions of attitudes towards economics education.…”
Section: Introductionmentioning
confidence: 99%
“…Major factors which affect the attitude of students toward technical subjects were interest, gender, socio-economic status among others. 127 Aysem and Fatma 115 reported that a significant relationship can be found between students’ attitude toward their study and many demographical variables. Micheal 128 reported that there is no evidence that there is a difference in the perception of male and female students on the four dimensions of attitudes towards economics education.…”
Section: Introductionmentioning
confidence: 99%
“…Technical education graduate is a skilled individual that operate machines and tools to carry out a giving task, whom acquired the knowledge and skills through training under the guidance of professionals (Backstein et al 2005;Azodo 2014;Van Laar et al 2017). It is assumed that individual that possess technical skills to immediately secure employment after graduation but lack of knowledge on emotional intelligence on the part of the technical education graduate and absence of specific instrument to measure the emotional intelligence for employment of technical education student is a major challenge facing the discipline.…”
Section: Introductionmentioning
confidence: 99%